Alleluia six part mixed chorus - McClellan, Robinson 1976- (See-a-Dot Music Publishing, 2014)
This piece is a more introspective and solemn approach to the traditional Alleluia, but maintains a strong melodic feel with soaring lines and a great mix of homophonic textures and counterpoint